Answer:
x = -
, x = 3
Explanation:
To find the zeros let p(x) = 0 , that is
2x² - 3x - 9 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 2 × - 9 = - 18 and sum = - 3
The factors are - 6 and + 3
Use these factors to split the x- term
2x² - 6x + 3x - 9 = 0 ( factor the first/second and third/fourth terms)
2x(x - 3) + 3(x - 3) = 0 ← factor out (x - 3) from each term
(x - 3)(2x + 3) = 0
Equate each factor to zero and solve for x
2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
x - 3 = 0 ⇒ x = 3